A New High Energy Lithium ion Batteries Consisting of 0.5Li2MnO3·0.5LiMn0.33Ni0.33Co0.33O2 and Soft Carbon Components. (10th March 2016) - Wang, Tao; Chen, Zhanjun; Zhao, Ruirui; Li, Aiju; Chen, Hongyu
Abstract: Electrochemical performance of the 18650 lithium-ion batteries consisting lithium-rich layered oxides 0.5Li2 MnO3 ·0.5LiMn0.33 Ni0.33 Co0.33 O2 cathode material and soft carbon anode is investigated in detail. The cathode is synthesized by a spray drying process and the properties are studied by various methods, while the soft carbon is commercial available. The assembled batteries can exhibit excellent cyclic performance with a capacity retention of 90.2% even after 600 cycles in the voltage ranges of 2.0-4.5 V (at 1C-rate). Moreover, they can also deliver excellent rate capabilities as the discharge capacity under 40C is nearly equal to 83.9% of that under 1C (voltage range is in 2.0-4.5 V). Furthermore, in order to evaluate the mechanism of the superior performance exhibited by the full cells, cells after 300 cycles are disassembled in a glove box to assess the changes on the active materials by using a series of technique methods, including a scanning electron microscopy (SEM), X-ray diffraction (XRD), energy dispersive spectrometry (EDS), High-resolution transmission electron microscope (TEM) and selected area electron diffraction (SAED).